The Concept of L2 User and the goals of Second Language Learning - Juanggo, Willy (Jurnal Studi Komunikasi, 2017)
It is generally considered that knowing one language is not enough in this era. People need to learn a second language in addition to their mother tongue to meet the demand of todayâ€™s life as many of them are becoming a part of multilingual society as well as to face the globalisation. This paper aims to demonstrate the reasons of people learning a second by looking at the several goals they want to achieve in current situation and link it to the second language learning in education context. Subsequently, it also provides some criticism against the majority of English language teachings that set native speakerâ€™s competence as the ultimate goal and highlights the concept of L2 user as a new paradigm and its implication to second language learning.Â